Evaluación de las aguas de drenaje del sector de riego de Tamarindo y su influencia sobre el Parque Nacional Palo Verde - Pérez-Castillo, Ana Gabriela (Universidad de Costa Rica, 2011)
The following physicochemical parameters were measured to determine the quality of the drainage water of Tamarindo Irrigation Sector, at the Arenal-Tempisque Irrigation District: temperature, pH, dissolved oxygen saturation percentage, electrical conductivity, chemical oxygen demand, concentration of suspended solids, nitrates and total phosphorous, as well as the concentration of zinc, fats and oils. The measurements were taken when it was estimated that drainage water had received the highest pollution loads from the surrounding paddy fields, during the second half of 2002 and the year 2003. The results were evaluated using the water quality index for the management of floodplain lakes (ICA-L). The water from Tamarindo Irrigation Sector, which entered the Palo Verde National Park (PNPV) through La Bocana lagoon, got an average value of ICA-Lp of 70. Relevant increases in total phosphorous concentration were found. Zinc generated a punctual pollution problem in the area of irrigation when it was applied to the rice during the dry season. The Chilo Campo sampling point and the La Bocana lagoon showed a continuous contamination with fats and oils, which would prevent its use in floodplain lagoons of PNPV. Comparison between the results obtained at the sampling points of Chilo Ocampo and La Bocana showed that the buffer zone exerts a beneficial effect, particularly regarding suspended solids, nitrates and total phosphorous (rainy season of 2002), but not enough to control the influence of polluting discharges from the irrigation system.